The status (quo) of VET in Brazil : an empirical study about its function, meaning and impingements from the perspective of former dual system apprentices - Kauer, Marcelo [Verfasser] (My University, 2015)
"The German dual system apprenticeship was adopted by the Instituto de Formação Profissional Administrativa (IFPA) School in Brazil, and has been recognized by the Brazilian government as a valid secondary level vocational education training (VET) program since 1996. This dissertation seeks to understand the conditions and mechanisms in the process that led former apprentices to undergo this German dual system, the analysis of the biography incumbents' discernment and experience within this VET program, as well as the biographical impingements this educational modality had on one's post-VET development. Therefore, this research was undertaken with the assistance of autobiographical narrative interviews, and has also employed the narrative analysis for interpretative purposes." (Author's abstract, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 1.3.1 Ausbildung im Dualen System; G 1.3.3 Bildungs- & Erwerbsbiografien; I 2.3.3 Lateinamerika; Berufsbildungssystem; Duales System; Ausbildungsabsolvent; Ausbildungsentscheidung; Berufsverlauf; Brasilien; Empirische Untersuchung